Godzilla (2011), volume 1 ebook - Swierczynski, Duane (Godzilla (2011), 2012)
Duane Swierczynski and Simon Gane launch this ultimate action-movie blockbuster, ushering in a new era of monster battles. Ex-special forces tough-guy Boxer is a man with a grudge and vows to end the terror of Godzilla, no matter what. He assembles a top-notch team to take down monster-sized threats... at $7 billion a bounty. What starts as a vendetta could become a lucrative business for Boxer... if he can live past day one! Collects Godzilla #1-4. Author: Duane Swierczynski. Illustrator: Simon Gane, Art Adams. © 2012 Toho Co., Ltd. All Rights Reserved. GODZILLA®, Gojira, the related characters and the Character Designs are trademarks of Toho Co., Ltd. © 2012 Idea and Design Works, LLC. All Rights Reserved.